Genotype Diversity, Wild Bird-to-Poultry Transmissions, and Farm-to-Farm Carryover during the Spread of the Highly Pathogenic Avian Influenza H5N1 in the Czech Republic in 2021/2022 - Nagy, Alexander; Stará, Martina; Černíková, Lenka; Hofmannová, Lada; Sedlák, Kamil (Viruses, 2023)
In 2021/2022, the re-emergence of highly pathogenic avian influenza (HPAI) occurred in Europe. The outbreak was seeded from two sources: resident and reintroduced viruses, which is unprecedented in the recorded history of avian influenza. The dominant subtype was H5N1, which replaced the H5N8 subtype that had predominated in previous seasons. In this study, we present a whole genome sequence and a phylogenetic analysis of 57 H5N1 HPAI and two low pathogenic avian influenza (LPAI) H5N1 strains collected in the Czech Republic during 2021/2022. Phylogenetic analysis revealed close relationships between H5N1 genomes from poultry and wild birds and secondary transmission in commercial geese. The genotyping showed considerable genetic heterogeneity among Czech H5N1 viruses, with six different HPAI genotypes, three of which were apparently unique. In addition, second-order reassortment relationships were observed with the direct involvement of co-circulating H5N1 LPAI strains. The genetic distance between Czech H5N1 HPAI and the closest LPAI segments available in the database illustrates the profound gaps in our knowledge of circulating LPAI strains. The changing dynamics of HPAI in the wild may increase the likelihood of future HPAI outbreaks and present new challenges in poultry management, biosecurity, and surveillance.
Keywords: H5N1; Phylogeny; Geese; poultry; highly pathogenic avian influenza; drůbež; virus chřipky A, podtyp H5N1; outbreak; Genotype; zvířata; Influenza A Virus, H5N1 Subtype; farmy; ptačí chřipka u ptáků; Poultry; husy; fylogeneze; Czech Republic; HPAI; Farms; genotyp; Animals; avian influenza; Česká republika; Influenza in Birds